The Role of Islamic Finance in Enhancing Financial Inclusion in Organization of Islamic Cooperation (OIC) Countries - Mohieldin, Mahmoud; Iqbal, Zamir; Rostom, Ahmed; Fu, Xiaochen (2012)
The core principles of Islam lay great emphasis on social justice, inclusion, and sharing of resources between the haves and the have nots. Islamic finance addresses the issue of "financial inclusion" or "access to finance" from two directions -- one through promoting risk-sharing contracts that provide a viable alternative to conventional debt-based financing, and the other through specific instruments of redistribution of the wealth among the society. Use of risk-sharing financing instruments can offer Shariah-compliant microfinance, financing for small and medium enterprises, and micro-insurance to enhance access to finance. And redistributive instruments such as Zakah, Sadaqat, Waqf, and Qard-al-hassan complement risk-sharing instruments to target the poor sector of society to offer a comprehensive approach to eradicating poverty and to build a healthy and vibrant economy. Instruments offered by Islam have strong historical roots and have been applied throughout history in various Muslim communities. The paper identifies gaps currently existing in Organisation of Islamic Cooperation (OIC) countries on each front, that is, Shariah-compliant micro-finance and financing for small and medium enterprises and the state of traditional redistributive instruments. The paper concludes that Islam offers a rich set of instruments and unconventional approaches, which, if implemented in true spirit, can lead to reduced poverty and inequality in Muslim countries plagued by massive poverty. Therefore, policy makers in Muslim countries who are serious about enhancing access to finance or "financial inclusion" should exploit the potential of Islamic instruments to achieve this goal and focus on improving the regulatory and financial infrastructure to promote an enabling environment.